MENGANALISIS RENCANA STRATEGIS MENUJU LEMBAGA PENDIDIKAN BERKUALITAS DAN KOMPETITIF - Mohamad Muspawi (Universitas Batanghari Jambi, 2015)
Having aquality education in stitutions and competitive is the ideal target of a management. Conduct an analysis of the strategic planis a strategic step that can be done by the manager. Managed to do a good analysis of the strategic plan means has made one important step for the advancement of educational institutions.Strategic planning is a discipline edeff or to make important decisions and actions that shape and guide how to be come an organization (or otherentity), whatever the organization (or otherentity), and why the organization (or otherentity) do such a thing(Bryson, 2007:4).The benef its of a strateg icplan for an organization (Bryson 2007:55) are as follows : a.Think strategic all and developeffective strategies. b. Clarify the direction of the future. c. Creatinga priority. d. Make the decision now to remember the future consequences. e. Develop a coherent and solid foundation fordecision-making. f. Using the maximum flexibility in are a sthatare under the control of the organization. g. Making decision sacross level sand functions.h. Solve the main problems of the organization. i. Improve the performance of the organization.j. Handle rapidly changing circum stances effectively. k. Build team work and expertise.Among the instrumentsthat can be used to analyze the strategic planare: SWOT analysisis an analysis that is used to look at the condition of organizations/institutions both in terms of strengths, weaknesses, opportunities and challenges/threats.And Balanced Score cardisanat tempt to direct the management and organization to look at the organization of approximately four perspectives: financial, customer, learning and growth, as well asinternal business linking short-termoperational control to the long-term vision and strategy.This paperaims to contribut etheir ide as on how to analyze the strategic planin order for the creation of a quality education a linstitution and competitive.Keywords: strategic plan, quality, competitive.